Assessment of Malnutrition in Cirrhotic Patients (Bangladesh Journal of Medical Science, 2016)
Malnutrition is a common but frequently overlooked problem among patients with cirrhosis of liver. Malnourished cirrhotic patients have a higher rate of complications and an overall increased mortality. Identifying these patients is of great clinical importance. This study was carried out to assess nutritional status of cirrhotic patients to identify those who are malnourished and to see the relationship between severity of liver disease and malnutrition. 105 patients were selected by purposive type sampling. Nutritional status was assessed by 3 anthropometric assessment tools- body mass index (BMI), mid upper arm muscle circumference (MAMC) and triceps skin fold thickness (TST). Severity of liver disease was assessed by Child-Pugh (CP) score. Severe malnutrition was defined as MAMC and TST